INOVASI PEMBUATAN PUPUK ORGANIK DARI TANDAN KOSONG KELAPA SAWIT DAN PUPUK KANDANG DI NAGARI SUNGAI KUNYIT KABUPATEN SOLOK SELATAN - Ferry Lismanto Syaiful; Alprian Alpred Siahaan; Resti Hidayati Putri (LPPM Universitas Andalas, 2022)
Nagari Sungai Kunyit, South Solok, is dubbed a plantation area. Most of the plantation land is in the form of oil palm plantations. The area of oil palm plantations in this village often increases the number of palm fruit and CPO produced, causing an abundance of palm oil waste products such as empty palm oil marks. However, the potential of this palm oil waste has not been utilized to make it a commodity that has economic value. For this reason, it is necessary to process the waste into compost. This activity aims to 1. increase the knowledge and ability of farmer groups in Sungai Kunyit Nagari processing empty fruit bunches of oil palm as organic fertilizer and 2. increase the motivation of farmer groups in Sungai Kunyit Nagari to use organic fertilizers in their agricultural cultivation business. This activity has been carried out in Nagari Sungai Kunyit, Sangir Balai Janggo District, South Solok Regency. The target of the activity is a farmer group in Nagari Sungai Kunyit, South Solok. The methods used in this activity are socialization/counseling, training, and evaluation. The results of this activity can increase the knowledge, skills, and understanding of partners in making organic fertilizers made from oil palm empty fruit bunches and manure. It can even increase farmer groups' motivation in Nagari Sungai Kunyit, South Solok, to make organic fertilizer. From the results of the activities that have been carried out, it can be concluded that the manufacture of organic fertilizers can be carried out with partners, which are made from empty oil palm bunches and manure. It is hoped that this can be sustainable to increase crop productivity.